Retrospective Study: Glycolic Acid Peel in Photoaging Patient - Brama Rachmantyo; Diah Mira Indramaya (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Photoaging is premature skin aging that is caused by sun exposure in long periode. Glycolic acid peel is one of photoaging treatment that improve skin at epidermal layer. Improper patient selection and irregular follow-up may become factors of unsuccessful treatment. Purpose: To evaluate gycolic acid peel treatment for photoaging for improvement of medical service in the future. Methods: A retrospective study to photoaging patiens that were managed with glicolyc acid peel in Medical Cosmeutic Division Dermatology and Venereology Departement Dr. Soetomo General Hospital Surabaya on period from January 2011 to December 2013. The data were collected from medical record, Results: New patient of photoaging is 455 patients in Medical Cosmetic Division, 15.8% patients were treated with glycolic acid peel. Diagnosis classification were using Glogau classification. Thirty six point one percent of patient did not undergo follow up and 47.1% of patient’s interval of follow up were more than 4 weeks. Majority of patient (37.5%) have no improvement. Conclusion: Education to photoaging patient that undergo glycolic acid peel need to be improved. Clinical worsening and no improvement in some patients may be caused by irregular follow up. Key words: photoaging, retrospective study, glycolic acid peel.